Interleukin-6 measured using the automated electrochemiluminescence immunoassay method for the identification of intra-amniotic inflammation in preterm prelabor rupture of membranes - Musilova, Ivana; Andrys, Ctirad; Holeckova, Magdalena; Kolarova, Veronika; Pliskova, Lenka; Drahosova, Marcela; Bolehovska, Radka; Pilka, Radovan; Huml, Karel; Cobo, Teresa; Jacobsson, Bo; Kacerovsky, Marian (Journal of maternal-fetal & neonatal medicine, 2020)
Introduction: We aimed to compare the amniotic fluid interleukin (IL)-6 concentrations measured using the automated electrochemiluminescence immunoassay method and ELISA, and to establish an IL-6 concentration cut-off value for intra-amniotic inflammation (IAI) in preterm prelabor rupture of membranes (PPROM), which can be used in the automated electrochemiluminescence immunoassay method.Materials and methods: A total of 120 women with PPROM were included in this study. Amniotic fluid samples were obtained through transabdominal amniocentesis. IL-6 concentrations were assessed using both the automated electrochemiluminescence immunoassay method and ELISA, the current gold standard. IAI was defined as an amniotic fluid IL-6 concentration of ≥2600 pg/mL measured using ELISA.Results: A correlation between both assays was found (Spearman's rho = 0.97; p < .0001). Based on the receiver-operating characteristic curve for the identification of IAI (area under the curve = 0.99), a cut-off value of ≥3000 pg/mL was selected for the automated electrochemiluminescence immunoassay method with a sensitivity of 88%, specificity of 99%, positive predictive value of 97%, negative predictive value of 96%, and likelihood ratio of 76.Conclusions: For amniotic fluid IL-6 concentrations assessed using the automated electrochemiluminescence immunoassay method, a cut-off value of 3000 pg/mL was indicated for diagnosing IAI in women with PPROM.
Keywords: Retrospective Studies; retrospektivní studie; Interleukin-6; Chorioamnionitis; Female; předčasný odtok plodové vody; Humans; lidé; Amniotic Fluid; Electrochemical Techniques; ELISA; ženské pohlaví; těhotenství; interleukin-6; senzitivita a specificita; Enzyme-Linked Immunosorbent Assay; Fetal Membranes, Premature Rupture; imunoanalýza; Biomarkers; biologické markery; chorioamnionitida; plodová voda; dospělí; Immunoassay; Adult; Pregnancy; Sensitivity and Specificity; elektrochemické techniky